Aculus sayanicus, a new species of Eriophyidae (Acari: Eriophyoidea) from grasses in Russia - Skoracka, Anna; Pacyna, Anna (Zootaxa, 2003)
A new species of Eriophyidae collected in Sayan Mountains in Russia is described and illustrated, based on adults of both sexes and the nymph. Aculus sayanicus n. sp. was found vagrant on Poa sibirica Roshev. A new host plant for Abacarus acutatus Sukhareva is recorded.